2020
DOI: 10.1097/01.nep.0000000000000635
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness Meditation and Anxiety in Nursing Students

Abstract: This quasi-experimental study used a convenience sample of nursing students (n = 49) to evaluate the effectiveness of mindfulness meditation on anxiety. Students participated in mindfulness meditation sessions and completed the State-Trait Anxiety Inventory. A statistically significant reduction in trait anxiety was found in the intervention group (p = .000); state anxiety decreased but not significantly. In contrast, anxiety increased significantly in the comparison group, but progression was not significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 5 publications
1
7
0
1
Order By: Relevance
“…Mindfulness refers to engagement or curiosity about the present moment, which encourages a non-judgmental attitude of openness and acceptance, thereby fostering balance and stillness (van der Riet, Levett-Jones, & Aquino-Russell, 2018). Several studies suggest that mindfulness meditation is an effective strategy for preventing and managing stress and burnout in the workplace, which often annoy nursing staff and practice students (Hoge et al, 2013;Hölzel et al, 2011;Stinson et al, 2020;Tang, Tang, & Posner, 2016;Zollars, Poirier, & Pailden, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mindfulness refers to engagement or curiosity about the present moment, which encourages a non-judgmental attitude of openness and acceptance, thereby fostering balance and stillness (van der Riet, Levett-Jones, & Aquino-Russell, 2018). Several studies suggest that mindfulness meditation is an effective strategy for preventing and managing stress and burnout in the workplace, which often annoy nursing staff and practice students (Hoge et al, 2013;Hölzel et al, 2011;Stinson et al, 2020;Tang, Tang, & Posner, 2016;Zollars, Poirier, & Pailden, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Mindfulness meditation defined as cultivating the habit of experiencing life consciously and mindfully in the present which focuses on the process meditatively (Stinson et al, 2020). Research conducted by Stinson et al, reported that there was a statistically significant decrease in the anxiety traits of nursing students with the mindfulness meditation intervention with a change in anxiety scores from 44.74 to 39.53.…”
Section: Mindfulness Meditationmentioning
confidence: 99%
“…Studies have shown that mindfulness strategies are associated with decreased stress and anxiety; some examples of mindfulness strategies are deep breathing, meditation, and mindful walking (Stinson et al, 2020). Aydin Sünbül (2020) describes "mindfulness as a significantly positive relationship with resilience, During the mental health had an increased focus that normalized the need for new practices to increase resilience.…”
Section: Brief Overview Of Mindfulnessmentioning
confidence: 99%
“…Hoy en día, el ámbito laboral juega un papel fundamental en la vida de todas las personas, ya que, es un lugar donde transcurre gran parte de nuestro tiempo. Existen ciertos trabajos que por su carácter de cara al público, situaciones de estrés y gran demanda social, presentan una mayor vulnerabilidad a desarrollar enfermedades o factores estresantes [1,2]. Es cierto que cierto nivel de estrés, en ocasiones puede resultar beneficioso para resolver situaciones con mayor efectividad y rapidez, sin embargo, cuando este se mantiene en el tiempo puede causar un efecto contrario [3,4].…”
Section: Introductionunclassified